Inserts and Cutting Tools

By optimizing the orientation of boron nitride planes and applying a metal nitride coating, the insert achieves improved wear resistance and extended tool life, addressing the wear issues of existing boron nitride sintered inserts.

JP7607673B2Active Publication Date: 2024-12-27KYOCERA CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022572092
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-25
Filing Date
2021-12-07
Publication Date
2024-12-27
Estimated Expiration
2041-12-07

AI Technical Summary

Technical Problem

Existing boron nitride sintered inserts suffer from poor wear resistance and performance as cutting tools due to the orientation of the (111) plane being strongly oriented, leading to increased wear and reduced effectiveness.

Method used

The insert incorporates a boron nitride sintered body with controlled amounts of cubic and compressed boron nitride, where the 002 plane of compressed boron nitride is oriented parallel to the surface, and a coating layer comprising a metal nitride structure for improved wear resistance and adhesion.

Benefits of technology

The insert exhibits enhanced wear resistance, hardness, and extended tool life due to the oriented 002 plane of compressed boron nitride and the robust coating layer, which prevents peeling and improves adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607673000003
    Figure 0007607673000003
  • Figure 0007607673000004
    Figure 0007607673000004
  • Figure 0007607673000005
    Figure 0007607673000005
Patent Text Reader

Abstract

In transmission X-ray diffraction with respect to a cross section of a boron nitride sintered body perpendicular to a first surface (7), let an X-ray intensity at the apex of a 111 diffraction peak of cubic boron nitride in a direction perpendicular to the first surface (7) be IcBN(111)v. Let an X-ray intensity at the apex of a 002 diffraction peak of compressed boron nitride be IhBN(002)v. Let an X-ray intensity at the apex of a 111 diffraction peak of cubic boron nitride in a direction parallel to the first surface (7) be IcBN(111)h. Let an X-ray intensity at the apex of a 002 diffraction peak of compressed boron nitride be IhBN(002)h. The compressed boron nitride content calculated from these X-ray intensities is greater than 0.002 and smaller than 0.01. A cubic orientation value is greater than 0.5, and a compressed boron nitride orientation value is greater than the cubic orientation value. Moreover, an insert (1) of the present disclosure has a coating layer (20) on at least part of the surface of the boron nitride sintered body.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an insert and a cutting tool. [Background technology]

[0002] Sintered boron nitride has high hardness, and due to this property, it is used for crushing members, tool inserts, etc.

[0003] Patent Document 1 describes a boron nitride sintered body containing cubic boron nitride. Patent Document 1 also describes a boron nitride sintered body containing wurtzite boron nitride and having an X-ray diffraction intensity I (111) X-ray diffraction intensity of the (220) face of cubic boron nitride I (220) Ratio I (220) / I (111) The present invention discloses a cubic boron nitride composite polycrystalline body having an orientation plane in which I is less than 0.1. In other words, in the orientation plane of the cubic boron nitride composite polycrystalline body, I (111) I (220) This is more than 10 times the oriented plane. In other words, it can be said that the (111) plane is strongly oriented in the oriented plane. This cubic boron nitride composite polycrystalline body is obtained by using oriented pBN as a raw material. In addition, when hexagonal boron nitride is included as a comparative example, it is described that even if the (111) plane is strongly oriented in the oriented plane of cubic boron nitride, the amount of wear is large and the performance as a cutting tool is inferior. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5929655 Summary of the Invention

[0005] An insert according to one embodiment of the present disclosure includes a boron nitride sintered body having a first surface, a second surface, and a cutting edge located at at least a part of an edge between the first surface and the second surface. The boron nitride sintered body contains cubic boron nitride and compressed boron nitride. In a transmission X-ray diffraction of a cross section of the boron nitride sintered body perpendicular to the first surface, the X-ray intensity at the apex of the 111 diffraction peak of cubic boron nitride in a direction perpendicular to the first surface is IcBN(111)v, the X-ray intensity at the apex of the 002 diffraction peak of compressed boron nitride in a direction parallel to the first surface is IcBN(111)h, and the X-ray intensity at the apex of the 002 diffraction peak of compressed boron nitride in a direction parallel to the first surface is IcBN(111)h. The compressive boron nitride content value represented by (IhBN(002)v+IhBN(002)h) / (IcBN(111)v+IcBN(111)h) is greater than 0.002 and less than 0.01. The cubic crystal orientation value represented by IcBN(111)v / (IcBN(111)v+IcBN(111)h) is greater than 0.5. The compressive boron nitride orientation value represented by IhBN(002)v / (IhBNv(002)+IhBN(002)h) is greater than the cubic crystal orientation value. In addition, the insert according to one embodiment of the present disclosure has a coating layer on at least a portion of the surface of the boron nitride sintered body.

[0006] A cutting tool according to one embodiment of the present disclosure includes a holder having a length extending from a first end to a second end and having a pocket on the first end side, and the above-mentioned insert positioned in the pocket. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a perspective view showing an example of an insert of the present disclosure. [Diagram 2] FIG. 2 is a perspective view showing another example of the insert of the present disclosure. [Diagram 3] FIG. 3 is a cross-sectional view showing an example of the configuration of the coating layer according to the present disclosure. [Figure 4] FIG. 4 is a schematic enlarged view of a portion H shown in FIG. [Diagram 5]FIG. 5 is a diagram showing an example of a cutting tool according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, a detailed description will be given of an embodiment (hereinafter, referred to as an "embodiment") for carrying out the insert and cutting tool according to the present disclosure with reference to the drawings. Note that the present disclosure is not limited to the embodiment. In addition, each embodiment can be appropriately combined as long as the processing contents are not contradictory. In addition, the same parts in each of the following embodiments are given the same reference numerals, and duplicated explanations will be omitted.

[0009] In addition, in the embodiments described below, expressions such as "constant", "orthogonal", "vertical" and "parallel" may be used, but these expressions do not necessarily mean "constant", "orthogonal", "vertical" and "parallel" strictly. In other words, each of the above expressions allows for deviations due to, for example, manufacturing accuracy and installation accuracy.

[0010] In addition, each of the drawings referred to below shows only the necessary main parts in a simplified manner for the sake of convenience of explanation.

[0011] Inserts made of sintered boron nitride are known. However, there is still room for improvement in terms of wear resistance of such inserts.

[0012] <insert> FIG. 1 shows an example of the insert 1 of the present disclosure. In the example shown in FIG. 1, the insert 1 is a polygonal boron nitride sintered body 3. FIG. 2 shows another example of the insert 1 of the present disclosure. FIG. 2 shows an example in which the boron nitride sintered body 3 is joined to a base 5 made of, for example, a cemented carbide alloy. The base 5, together with the boron nitride sintered body 3, forms a polygonal insert. With such a configuration, the proportion of the relatively expensive boron nitride sintered body 3 in the insert 1 can be reduced. In the example shown in FIG. 2, the boron nitride sintered body 3 is located at one of the multiple corners of the insert 1. However, the boron nitride sintered body 3 may be located at two or more of the multiple corners of the insert 1.

[0013] A bonding material (not shown) containing, for example, Ti or Ag may be located between the boron nitride sintered body 3 and the base body 5. The boron nitride sintered body 3 and the base body 5 can be integrated together via the bonding material using a conventionally known bonding method.

[0014] The boron nitride sintered body 3 has a first surface 7 and a second surface 9. In the example shown in Figs. 1 and 2, the first surface 7 is the top surface of the insert 1, and the second surface is the side surface of the insert 1. In the example shown in Figs. 1 and 2, the first surface 7 corresponds to the rake surface, and the second surface 9 corresponds to the flank surface. Hereinafter, the first surface 7 may be referred to as the rake surface 7. Also, the second surface 9 may be referred to as the flank surface 9. The insert 1 has a cutting edge 13 on at least a part of the ridge between the first surface 7 and the second surface 9.

[0015] The boron nitride sintered body 3 in the insert 1 of the present disclosure contains cubic boron nitride and compressive boron nitride.

[0016] Among the data obtained by transmission X-ray diffraction on a cross section perpendicular to the first surface 7 of the boron nitride sintered body 3, the X-ray intensity of the 111 diffraction of cubic boron nitride in a direction perpendicular to the first surface 7 is defined as IcBN(111)v. In addition, the X-ray intensity of the 002 diffraction of compressive boron nitride in a direction perpendicular to the first surface 7 is defined as IhBN(002)v. In addition, among the data obtained by transmission X-ray diffraction on a cross section perpendicular to the first surface 7 of the boron nitride sintered body 3, the X-ray intensity of the 111 diffraction of cubic boron nitride in a direction parallel to the first surface 7 is defined as IcBN(111)h. In addition, the X-ray intensity of the 002 diffraction of compressive boron nitride in a direction parallel to the first surface 7 is defined as IhBN(002)h.

[0017] The above surface specifications are based on JCPDS Card No. 01-075-6381 for cubic boron nitride, JCPDS Card No. 18-251 for compressed boron nitride, JCPDS Card No. 00-045-0893 for hexagonal boron nitride, and JCPDS Card No. 00-049-1327 for wurtzite boron nitride, which will be described later.

[0018] The transmission X-ray diffraction may be carried out using, for example, a curved IPX-ray diffraction device RINT RAPID2 manufactured by Rigaku Corporation.

[0019] (IhBN(002)v+IhBN(002)h) / (I(111)v+IcBN(111)h) obtained based on the above X-ray intensities is called the compressive boron nitride content. The compressive boron nitride content is an index related to the amount of compressive boron nitride contained in the boron nitride sintered compact 3. The larger this value is, the greater the amount of compressive boron nitride contained in the boron nitride sintered compact 3. The compressive boron nitride content is not the amount of content itself.

[0020] The boron nitride sintered body 3 in the insert 1 of the present disclosure has a compressive boron nitride content value greater than 0.002 and less than 0.01. That is, the boron nitride sintered body 3 in the insert 1 of the present disclosure contains compressive boron nitride to an extent that satisfies this condition.

[0021] In addition, IcBN(111)v / (IcBN(111)v+IcBN(111)h) obtained based on the above X-ray intensities is called the cubic orientation value. When the cubic orientation value is 0.5, the 111 planes of the cubic boron nitride are randomly oriented and are in a non-oriented state. The larger the cubic orientation value, the greater the degree to which the 111 planes of the cubic boron nitride contained in the boron nitride sintered body 3 are oriented parallel to the first surface 7.

[0022] The boron nitride sintered body 3 in the insert 1 of the present disclosure has a cubic orientation value of greater than 0.5. In other words, the X-ray intensity at the apex of the 111 diffraction peak of cubic boron nitride in the perpendicular direction is greater than the X-ray intensity at the apex of the 111 diffraction peak of cubic boron nitride in the parallel direction. In other words, it can be said that the 111 plane of cubic boron nitride is oriented along the normal direction of the first surface 7.

[0023] IhBN(002)v / (IhBN(002)v+IhBN(002)h) obtained based on the above X-ray intensities is called the compressed boron nitride orientation value. When the compressed boron nitride orientation value is 0.5, the 002 plane of the compressed boron nitride faces in a random direction and is in a non-oriented state. The larger the compressed boron nitride orientation value, the greater the degree to which the 002 plane of the compressed boron nitride contained in the boron nitride sintered body 3 is oriented parallel to the first surface 7.

[0024] The boron nitride sintered body 3 in the insert 1 of the present disclosure has a compressive boron nitride orientation value greater than a cubic orientation value, i.e., the 002 plane of the compressive boron nitride is more oriented parallel to the first surface 7 than the 111 plane of the cubic boron nitride.

[0025] The insert 1 of the present disclosure has the above-mentioned configuration and thus has excellent wear resistance. This effect is presumably due to the fact that the insert 1 of the present disclosure contains a small amount of compressed boron nitride and furthermore, the 002 plane of the compressed boron nitride is largely oriented on the first surface, so that the workpiece welded to the first surface is peeled off together with the compressed boron nitride.

[0026] The boron nitride sintered body 3 in the insert 1 of the present disclosure may have a compressed boron nitride content of 0.004 or more and 0.008 or less. With this configuration, the insert 1 has high hardness.

[0027] Moreover, the boron nitride sintered body 3 in the insert 1 of the present disclosure may have a cubic orientation value of 0.55 or more. With such a configuration, the hardness of the rake face 7 is high.

[0028] The boron nitride sintered body 3 in the insert 1 of the present disclosure may have a compressed boron nitride orientation value of 0.8 or more. With this configuration, the insert 1 has a long life.

[0029] In the insert 1 of the present disclosure, the boron nitride sintered body 3 may contain wurtzite type boron nitride. The boron nitride sintered body 3 having such a structure has high hardness.

[0030] In addition, the insert 1 of the present disclosure may have an average grain size of cubic boron nitride of 200 nm or less. With such a configuration, the insert 1 has high strength. The average grain size of cubic boron nitride may be 100 nm or less.

[0031] Moreover, the insert 1 of the present disclosure may have a hard coating layer (not shown) on the surface of the boron nitride sintered body 3 .

[0032] <Coating layer> The insert 1 of the present disclosure may have a coating layer. The coating layer is applied to the boron nitride sintered body 3 for the purpose of improving the wear resistance, heat resistance, etc. of the boron nitride sintered body 3. In the insert 1 shown in FIG. 2, the coating layer may be applied to the boron nitride sintered body 3 and the base body 5.

[0033] Here, an example of the configuration of the coating layer of the insert 1 will be described with reference to Fig. 3. Fig. 3 is a cross-sectional view showing an example of the configuration of the coating layer of the present disclosure.

[0034] 3, the insert 1 has a coating layer 20. The thickness of the coating layer 20 may be, for example, not less than 0.1 μm and not more than 5.0 μm.

[0035] The coating layer 20 has a hard layer 21. The hard layer 21 is a layer having superior wear resistance compared to the metal layer 22 described later. The hard layer 21 has one or more metal nitride layers. The hard layer 21 may be a single layer. Also, as shown in FIG. 3, a plurality of metal nitride layers may be overlapped. Also, the hard layer 21 may have a laminated portion 23 in which a plurality of metal nitride layers are laminated, and a third metal nitride layer 24 located on the laminated portion 23. The configuration of the hard layer 21 will be described later.

[0036] Moreover, the coating layer 20 has a metal layer 22. The metal layer 22 is located between the boron nitride sintered body 3 and the hard layer 21. Specifically, the metal layer 22 contacts the upper surface of the boron nitride sintered body 3 at a first surface (here, the lower surface), and contacts the lower surface of the hard layer 21 at a second surface (here, the upper surface) located opposite the first surface.

[0037] The metal layer 22 has higher adhesion to the boron nitride sintered body 3 than the hard layer 21. Examples of metal elements having such properties include Zr, V, Cr, W, Al, Si, and Y. The metal layer 22 contains at least one of the above metal elements.

[0038] Note that simple elements of Ti, Zr, V, Cr, and Al are not used as the metal layer 22. These elements all have low melting points and low oxidation resistance, making them unsuitable for use in cutting tools. Also, simple elements of Hf, Nb, Ta, and Mo have low adhesion to the boron nitride sintered body 3. However, this does not apply to alloys containing Ti, Zr, V, Cr, Ta, Nb, Hf, and Al.

[0039] The metal layer 22 may be an Al-Cr alloy layer containing an Al-Cr alloy. Such a metal layer 22 has a particularly high adhesion to the boron nitride sintered body 3, and is therefore highly effective in improving the adhesion between the boron nitride sintered body 3 and the coating layer 20.

[0040] When the metal layer 22 is an Al-Cr alloy layer, the Al content in the metal layer 22 may be greater than the Cr content in the metal layer 22. For example, the composition ratio (atomic %) of Al to Cr in the metal layer 22 may be 70:30. With such a composition ratio, the adhesion between the boron nitride sintered body 3 and the metal layer 22 is higher.

[0041] The metal layer 22 may contain components other than the above metal elements (Zr, V, Cr, W, Al, Si, Y). However, from the viewpoint of adhesion to the boron nitride sintered body 3, the metal layer 22 may contain at least 95 atomic % or more of the above metal elements in total. More preferably, the metal layer 22 may contain at least 98 atomic % or more of the above metal elements in total. For example, when the metal layer 22 is an Al-Cr alloy layer, the metal layer 22 may contain at least Al and Cr in total of 95 atomic % or more. Furthermore, the metal layer 22 may contain at least Al and Cr in total of 98 atomic % or more. The ratio of the metal components in the metal layer 22 can be identified, for example, by analysis using EDS (energy dispersive X-ray spectrometry).

[0042] Moreover, since Ti has poor wettability with the boron nitride sintered body 3, it is preferable that the metal layer 22 contains as little Ti as possible from the viewpoint of improving adhesion with the boron nitride sintered body 3. Specifically, the Ti content in the metal layer 22 may be 15 atomic % or less.

[0043] In this manner, in the insert 1 of the present disclosure, the metal layer 22, which has higher wettability with the boron nitride sintered body 3 than the hard layer 21, is provided between the boron nitride sintered body 3 and the hard layer 21, thereby improving the adhesion between the boron nitride sintered body 3 and the coating layer 20. Since the metal layer 22 also has high adhesion with the hard layer 21, the hard layer 21 is unlikely to peel off from the metal layer 22.

[0044] Moreover, the boron nitride sintered body 3 is an insulator. The boron nitride sintered body 3, which is an insulator, has room for improvement in adhesion with a film formed by a PVD method (physical vapor deposition). In contrast, the insert 1 of the present disclosure has a conductive metal layer 22 located on the surface of the boron nitride sintered body 3, so that the adhesion between the hard layer 21 formed by the PVD method and the metal layer 22 is high.

[0045] Next, the configuration of the hard layer 21 will be described with reference to Fig. 4. Fig. 4 is a schematic enlarged view of a portion H shown in Fig. 3.

[0046] As shown in FIG. 4, the hard layer 21 has a laminated portion 23 located on the metal layer 22, and a third metal nitride layer 24 located on the laminated portion 23.

[0047] The laminated portion 23 has a plurality of first metal nitride layers 23a and a plurality of second metal nitride layers 23b. The laminated portion 23 has a configuration in which the first metal nitride layers 23a and the second metal nitride layers 23b are alternately laminated.

[0048] The thickness of the first metal nitride layer 23a and the second metal nitride layer 23b may be 10 nm or more and 50 nm or less, respectively. In this way, by forming the first metal nitride layer 23a and the second metal nitride layer 23b thin, the residual stress of the first metal nitride layer 23a and the second metal nitride layer 23b is small. As a result, for example, peeling or cracking of the first metal nitride layer 23a and the second metal nitride layer 23b is less likely to occur, and the durability of the coating layer 20 is high.

[0049] The first metal nitride layer 23a is a layer in contact with the metal layer 22, and the second metal nitride layer 23b is formed on the first metal nitride layer 23a.

[0050] The first metal nitride layer 23a and the second metal nitride layer 23b may contain the metal contained in the metal layer 22.

[0051] For example, suppose that metal layer 22 contains two types of metals (herein referred to as a "first metal" and a "second metal"). In this case, first metal nitride layer 23a contains nitrides of the first metal and a third metal. The third metal is a metal not contained in metal layer 22. In addition, second metal nitride layer 23b contains nitrides of the first metal and the second metal.

[0052] For example, in the embodiment, the metal layer 22 may contain Al and Cr. In this case, the first metal nitride layer 23a may contain Al. Specifically, the first metal nitride layer 23a may be an AlTiN layer containing AlTiN, which is a nitride of Al and Ti. Also, the second metal nitride layer 23b may be an AlCrN layer containing AlCrN, which is a nitride of Al and Cr.

[0053] In this manner, by positioning the first metal nitride layer 23a containing the metal contained in the metal layer 22 on the metal layer 22, the adhesion between the metal layer 22 and the hard layer 21 is high. This makes it difficult for the hard layer 21 to peel off from the metal layer 22, and therefore the durability of the coating layer 20 is high.

[0054] The first metal nitride layer 23a, i.e., the AlTiN layer, has excellent adhesion to the metal layer 22, for example, in wear resistance. The second metal nitride layer 23b, i.e., the AlCrN layer, has excellent heat resistance and oxidation resistance, for example. In this way, the coating layer 20 includes the first metal nitride layer 23a and the second metal nitride layer 23b, which have different compositions, and thus the characteristics of the hard layer 21, such as wear resistance and heat resistance, can be controlled. This can extend the tool life of the insert 1. For example, in the hard layer 21 according to the embodiment, mechanical properties, such as adhesion to the metal layer 22 and wear resistance, can be improved while maintaining the excellent heat resistance of AlCrN.

[0055] In this manner, at least a portion of coating layer 20 may be a laminate of a plurality of layers (first metal nitride layer 23a and second metal nitride layer 23b) each having a thickness of 10 nm or more and 50 nm or less.

[0056] The laminated portion 23 may be formed by, for example, an arc ion plating method (AIP method). The AIP method uses arc discharge in a vacuum atmosphere to evaporate target metals (here, an AlTi target and an AlCr target), and then deposits N 2 This is a method for forming a film of metal nitride (here, AlTiN and AlCrN) by combining with a gas. The metal layer 22 may also be formed by the AIP method.

[0057] The third metal nitride layer 24 may be located on the laminated portion 23. Specifically, the third metal nitride layer 24 contacts the second metal nitride layer 23b of the laminated portion 23. The third metal nitride layer 24 is, for example, a metal nitride layer containing Ti and Al (AlTiN layer) like the first metal nitride layer 23a.

[0058] The thickness of the third metal nitride layer 24 may be thicker than the thicknesses of the first metal nitride layer 23a and the second metal nitride layer 23b. Specifically, when the thicknesses of the first metal nitride layer 23a and the second metal nitride layer 23b are 50 nm or less as described above, the thickness of the third metal nitride layer 24 may be 1 μm or more. For example, the thickness of the third metal nitride layer 24 may be 1.2 μm.

[0059] Thereby, for example, when the friction coefficient of the third metal nitride layer 24 is low, the adhesion resistance of the insert 1 can be improved. Also, for example, when the hardness of the third metal nitride layer 24 is high, the wear resistance of the insert 1 can be improved. Also, for example, when the oxidation onset temperature of the third metal nitride layer 24 is high, the oxidation resistance of the insert 1 can be improved.

[0060] Furthermore, the thickness of third metal nitride layer 24 may be thicker than the thickness of laminated portion 23. Specifically, in the embodiment, when the thickness of laminated portion 23 is 0.5 μm or less, the thickness of third metal nitride layer 24 may be 1 μm or more. For example, when the thickness of laminated portion 23 is 0.3 μm, the thickness of third metal nitride layer 24 may be 1.2 μm. In this way, by making third metal nitride layer 24 thicker than laminated portion 23, the effect of improving the above-mentioned adhesion resistance, wear resistance, etc. is further enhanced.

[0061] The thickness of metal layer 22 may be, for example, not less than 0.1 μm and less than 0.6 μm. That is, metal layer 22 may be thicker than each of first metal nitride layer 23a and second metal nitride layer 23b, and thinner than stacked portion 23.

[0062] <Cutting tools> Next, the cutting tool of the present disclosure will be described with reference to Fig. 5. Fig. 5 is a diagram showing an example of the cutting tool of the present disclosure.

[0063] As shown in FIG. 5, the cutting tool 101 of the present disclosure is, for example, a rod-shaped body extending from a first end (upper end in FIG. 5) to a second end (lower end in FIG. 5).

[0064] 5, the cutting tool 101 has a length extending from a first end (tip) to a second end, and includes a holder 105 having a pocket 103 located on the first end side, and the above-mentioned insert 1 located in the pocket 103. Since the cutting tool 101 includes the insert 1, it is possible to perform stable cutting processing for a long period of time.

[0065] The pocket 103 is a portion in which the insert 1 is attached, and has a seating surface parallel to the lower surface of the holder 105 and a constraining side surface that is perpendicular to the seating surface or inclined to the seating surface. The pocket 103 is open on the first end side of the holder 105.

[0066] The insert 1 is positioned in the pocket 103. At this time, the lower surface of the insert 1 may be in direct contact with the pocket 103, or a sheet (not shown) may be sandwiched between the insert 1 and the pocket 103.

[0067] The insert 1 is attached to the holder 105 so that at least a part of a portion used as the cutting edge 13 at the ridge where the rake face 7 and the flank face 9 intersect protrudes outward from the holder 105. In this embodiment, the insert 1 is attached to the holder 105 by a fixing screw 107. That is, the fixing screw 107 is inserted into the through hole 55 of the insert 1, and the tip of the fixing screw 107 is inserted into a screw hole (not shown) formed in the pocket 103 to screw the threaded portions together, thereby attaching the insert 1 to the holder 105.

[0068] The holder 105 may be made of steel, cast iron, etc. Among these materials, steel may be used because of its high toughness.

[0069] In this embodiment, a cutting tool used for so-called turning is exemplified. Examples of turning include inner diameter machining, outer diameter machining, and grooving. The cutting tool is not limited to the one used for turning. For example, the insert 1 of the above embodiment may be used for a cutting tool used for milling.

[0070] <Manufacturing method> The manufacturing method of the boron nitride sintered body in the insert of the present disclosure will be described below. First, a flat hexagonal boron nitride powder is prepared as a raw material powder. The average particle size of the hexagonal boron nitride powder is 0.7 μm or more, and the amount of oxygen impurities is less than 0.5 mass% among commercially available raw materials. The average particle size of the hexagonal boron nitride powder means the average value of the length of the long axis direction of the boron nitride powder measured by an electron microscope. The hexagonal boron nitride powder may have an average particle size of 0.2 μm or more and 30 μm or less. The hexagonal boron nitride powder may be high purity with a purity of 99% or more. It may also contain a catalyst component used in manufacturing cubic boron nitride powder. A raw material powder with a purity of less than 99% may also be used.

[0071] The raw material powder is molded using a uniaxial press, and by controlling the pressure during molding, the cubic crystal orientation value and compressed boron nitride orientation value after sintering can be controlled. When molded using a uniaxial press, the flat hexagonal boron nitride powder is oriented so that the 002 plane of the hexagonal boron nitride powder is oriented perpendicular to the pressure axis direction of the press. When applying pressure repeatedly to the same molded body during uniaxial pressing, the orientation of the hexagonal boron nitride powder in the molded body is high.

[0072] Next, the molded body produced by the above method is sintered at a temperature of 1800 to 2200°C and a pressure of 8 to 10 GPa to obtain the boron nitride sintered body of the present disclosure. The ratio of compressed boron nitride contained in the boron nitride sintered body can be controlled by the temperature and pressure during sintering. Furthermore, a coating layer can be formed on the boron nitride sintered body by the above manufacturing method.

[0073] The boron nitride sintered body, insert, and cutting tool of the present disclosure have been described above, but they are not limited to the above-described embodiments, and various improvements and modifications may be made without departing from the gist of the present disclosure. EXAMPLES

[0074] Flat hexagonal boron nitride powder with average particle sizes of 0.3 μm, 6 μm, and 16 μm and oxygen impurity content of 0.3 mass% was molded into compacts using a uniaxial press. The same hexagonal boron nitride powder was also pressed isostatically to produce compacts. These compacts were sintered under the conditions shown in Table 1.

[0075] Next, the obtained sintered body was cut in a direction perpendicular to the first surface of the sintered body to prepare a test piece having a thickness of about 0.5 mm and a surface perpendicular to the first surface. The compressed boron nitride content, cubic crystal orientation, and compressed boron nitride orientation were determined using a curved IPX-ray diffractometer RINT RAPID2 manufactured by Rigaku Corporation, based on a cross section perpendicular to the first surface of the test piece. The obtained values ​​are shown in Table 1. Furthermore, a part of the obtained sintered body was cut out to prepare an insert. A sample was also prepared in which a coating layer was provided on the surface of the insert. The composition of this coating layer is shown in Table 2. In the following test, an insert without a coating layer and an insert with two types of coating layers were evaluated. [Table 1] [Table 2]

[0076] The cutting tests were carried out using the first faces of these inserts as the rake faces. The conditions of the cutting tests are as follows:

[0077] <Cutting test conditions> Work material: Ti alloy (Ti-6Al-4V) Cutting conditions: Vc=100m / min, f=0.1mm / rev, ap=0.4mm, Wet Tool used: CNGA120408

[0078] None of the samples Nos. 1 to 3, 7, 11, and 15 obtained from isostatically pressed compacts have the configuration of the boron nitride sintered body in the insert of the present disclosure. Even when a uniaxially pressed compact was used, samples Nos. 8 to 10, which were fired at a temperature of 2100°C and a pressure of 11 GPa, did not contain compressed boron nitride. Sample No. 16, which was fired at a temperature of 2300°C and a pressure of 7.7 GPa using a uniaxially pressed compact, contained compressed boron nitride, but the orientation value of the compressed boron nitride was smaller than the cubic orientation value.

[0079] On the other hand, among the samples formed by uniaxial pressing, samples Nos. 4 to 6 and 12 to 14 had a compressed boron nitride content value less than 0.005, a cubic orientation value greater than 0.5, a compressed boron nitride orientation value greater than the cubic orientation value, and a long life. The average grain size of the cubic boron nitride in samples Nos. 4 to 6 and 12 to 14 was all 200 nm or less. In particular, the average grain size of sample No. 4 and sample No. 12, which used raw material powder with a small average grain size, was 100 nm or less.

[0080] Samples Nos. 5, 6, 12, 13, and 14, which have a cubic orientation value of 0.55 or more, had longer life spans than sample No. 4, which had a cubic orientation value of less than 0.55. Samples Nos. 13 and 14, which have a compressed boron nitride orientation value of 0.8 or more, had longer life spans than sample No. 12, which had a compressed boron nitride orientation value of less than 0.8.

[0081] The samples not satisfying the constituent requirements of the boron nitride sintered body in the insert of the present disclosure had a shorter life than the inserts of the present disclosure, samples Nos. 4 to 6 and 12 to 14. In all samples, the inserts having a coating layer had a longer life than the inserts not having a coating layer. In particular, the inserts having a metal layer had a longer life.

[0082] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. Indeed, the above-described embodiments may be embodied in various forms. Furthermore, the above-described embodiments may be omitted, substituted, or modified in various forms without departing from the scope and spirit of the appended claims. [Explanation of symbols]

[0083] 1. Insert 3. Boron nitride sintered body 5...Base 7. Rake face 9. Flank 13...Cutting edge 20...Covering layer 21...Hard layer 22...metal layer 23...Laminated section 23a First metal nitride layer 23b: Second metal nitride layer 24...Third metal nitride layer 101·Cutting tools 103 Pocket 105··Holder

Claims

1. An insert comprising a boron nitride sintered body having a first surface, a second surface, and a cutting edge located at at least a portion of a ridge between the first surface and the second surface, The boron nitride sintered body contains cubic boron nitride and compressed hexagonal boron nitride, In a transmission X-ray diffraction analysis of a cross section of the boron nitride sintered body perpendicular to the first surface, the X-ray intensity at the apex of the 111 diffraction peak of the cubic boron nitride in a direction perpendicular to the first surface is defined as IcBN(111)v, and the X-ray intensity at the apex of the 002 diffraction peak of the compressed hexagonal boron nitride is defined as IhBN(002)v; When the X-ray intensity at the apex of the 111 diffraction peak of the cubic boron nitride in a direction parallel to the first surface is IcBN(111)h and the X-ray intensity at the apex of the 002 diffraction peak of the compressed hexagonal boron nitride is IhBN(002)h, the compressive hexagonal boron nitride content, represented by (IhBN(002)v+IhBN(002)h) / (IcBN(111)v+IcBN(111)h), is greater than 0.002 and less than 0.01; The cubic orientation value, IcBN(111)v / (IcBN(111)v+IcBN(111)h), is greater than 0.5; the compressed hexagonal boron nitride orientation value, represented by IhBN(002)v / (IhBN(002)v+IhBN(002)h), is greater than the cubic orientation value; The boron nitride sintered body has a coating layer on at least a part of a surface thereof, The thickness of the coating layer is 0.1 μm or more and 5.0 μm or less.

2. The insert of claim 1 , wherein the cubic orientation value is 0.55 or greater.

3. 3. The insert of claim 1 or 2, wherein the compressed hexagonal boron nitride has an orientation value of 0.8 or greater.

4. The insert according to any one of claims 1 to 3, wherein the boron nitride sintered body contains wurtzite type boron nitride.

5. An insert according to any one of claims 1 to 4, wherein the average grain size of the cubic boron nitride in the cross section is less than or equal to 200 nm.

6. 6. The insert according to claim 1, wherein the coating layer has a plurality of laminated layers, and the coating layer in contact with the boron nitride sintered body is formed of a metal.

7. 7. The insert according to claim 6, wherein the metal is a metal other than the simple elements Ti, Zr, V, Cr, Ta, Nb, Hf, and Al.

8. 8. The insert according to claim 7, wherein the metal contains at least one of the following elements: Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, Y.

9. The insert according to any one of claims 1 to 8, wherein at least a portion of the coating layer is formed by laminating a plurality of layers, each layer having a thickness of 10 nm or more and 50 nm or less.

10. a holder having a length extending from a first end to a second end and having a pocket on the first end side; A cutting tool comprising: an insert according to any one of claims 1 to 9 located in the pocket.

Citation Information

Patent Citations

  • Preparation of beta-mercaptopropionic acid

    JP1984029655A

  • Boron nitride polycrystalline body, method for producing the same, and tool

    JP2014084243A

  • Cubic boron nitride composite sintered body, production method thereof and cutting tool, abrasion-resistant tool and grinding tool

    JP2015202981A

  • Boron nitride polycrystal and tool

    JP2016128378A

  • Boron nitride-based sintered body, insert and cutting tool

    JP2020158361A